Mesane Tümörünü Taklit Eden Eozinofilik Sistit Olgusu - Taşdemir, Cemal; Onur, Rahmi; Tuygun, Uğur Oktay; Orhan, İrfan (Fırat University, 2004)
Eozinofilik sistit nadir görülen ve genellikle allerjik öyküsü olan hastalarda ortaya çıkan, mesanenin inflamatuar bir hastalığıdır. Literatürde oldukça az rastlanılan bu durumda hastalar sıklıkla alt üriner sistem şikayetleri ile başvurur. Bu durum radyolojik incelemelerde nadiren mesanede kitle veya mesane duvarı kalınlaşmasına neden olarak mesane tümörüyle karışabilir. Bu çalışmada, kırk-sekiz yaşında erkek hastada hematüriye neden olan ve radyolojik olarak mesane tümörünü taklit eden eozinofilik sistit olgusu sunulmuştur. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Eosiniphilic cystitis is rare inflammatory disease of bladder that is most commonly encountered in patients with a history of allergy. Few cases were reported in literature and patients present mainly with symptoms of lower urinary tract. It rarely leads to development of a mass in bladder or thickening of bladder wall, but may be confused with bladder tumor, In this study, we presented a forty-eight years-old male patient with hematuria and radiological evidence of bladder mass mimicking bladder tumor , who was subsequently diagnosed as eosinophilic cystitis. ©2004, Fırat Üniversitesi, Tıp Fakültesi
A Case of Eosinophilic a Cystitis Mimicking Bladder Tumor